2008
DOI: 10.1159/000129604
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes Mellitus among Kuwaiti Children and Adolescents

Abstract: Objectives: To determine the prevalence of type 2 diabetes among 6- to 18-year-old Kuwaiti children. Subjects and Methods: Children with type 2 diabetes were identified at 182 schools (50 primary, 63 intermediate, and 69 secondary) randomly selected using the 2000/2001 educational districts’ registers as a sampling frame. Prevalence rates were adjusted to the 2002 Kuwaiti population. Diagnosis of type 2 diabetes was based on the World Health Organization and the American Diabetes Association criteria. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…WC is a sensitive measure of abdominal fat (2,3,7) . Several experts recommend that WC should be used for children and adults when screening for potential CVD and T2DM risk (6)(7)(8)15,19,23) . WC cut-off values have been proposed for children and adolescents of several Western countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WC is a sensitive measure of abdominal fat (2,3,7) . Several experts recommend that WC should be used for children and adults when screening for potential CVD and T2DM risk (6)(7)(8)15,19,23) . WC cut-off values have been proposed for children and adolescents of several Western countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Given the precipitous increase in overweight and obesity in Kuwait (15)(16)(17)(18) , the use of these curves and tables can provide early identification of children who may be at higher risk for future CVD and T2DM (6,8) . We found that male children had higher WC percentiles than female children at most of the ages that were studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of two health regions, Mubarak and Farwaniya, reported the prevalence of type 2 diabetes to be 26.3% among Kuwaitis aged 6 60 years [5] . Among children and youths aged 6-18 years, the prevalence of type 2 diabetes was reported to be 34.9/100,000 in 2000-2002 [6] .…”
mentioning
confidence: 99%
“…Studies indicate a genetic connection for DM2 development (17)(18)(19) . One study carried out with children and adolescents in Kuwait found a statistically significant (p=0.004) association between DM2 in this population and DM2 family history (20) . Additionally, adolescents who have a maternal antecedent of DM2 have 3.10 times more chances of developing the disease compared with a paternal antecedent (2.54) (18) , though contradictory results have been found in other studies whose ethnical groups present a high prevalence of the disease (3,6) .…”
Section: Discussionmentioning
confidence: 69%